G318(P) British society of paediatric and adolescent rheumatology (BSPAR) standards of care for uveitis screening in children with juvenile idiopathic arthritis (JIA) – compliance in a single centre in southern Ireland. (25th October 2020) - O' Sullivan, D; Foley, C; Deely, DA; Felsenstein, S
Abstract : Background: Uveitis is an extra-articular manifestation of Juvenile Idiopathic Arthritis (JIA) that affects up to 30% of patients. Presentation is classically insidious and may cause blindness. It is essential that regular slit-lamp examination is performed in all cases of JIA. BSPAR/Royal College of Ophthalmology (RCO) Uveitis Screening principles recommend following JIA diagnosis, slit-lamp examination should occur; Immediately and no later than 6 weeks from referral (recommendation 1) Every 2 months, from onset of arthritis, for 6 months (recommendation 2) Every 3–4 months thereafter (recommendation 3) Aims: To describe compliance with BSPAR/RCO guidelines in newly diagnosed cases of JIA. Methodology: A retrospective chart review of children with JIA attending our Centre was performed to ascertain compliance with BSPAR/RCO guidelines. Results: 28 children with a diagnosis of JIA attend our Centre (Female n=23, 82%). Nine patients were ANA positive (28%). Classification of patients identified 39% (n=11) had polyarticular JIA, 22% (n=6) had Oligoarticular JIA, 14% (n=4) had systemic onset JIA, 14% (n=4) had Psoriatic JIA and 11% (n=3) had enthesitis-related arthritis. Table 1 details results of compliance with BSPAR/RCO guidelines. Discussion: Current practice at our Centre, as judged against the BSPAR/RCO standards of care, is suboptimal. We report a delay in access to an Ophthalmologist for initial slit-lamp examination following JIA diagnosis and follow-up reviews are less frequent than is best practice. This audit has highlighted need for improvement in the provision of care for our patients with JIA and we intend to utilise this data as the basis for future quality improvement initiatives.